Improvement of Uniaxial Compression of Soil with ZnO tetrapods - Rizvi Z.H.; Nissar N.; Giri Prasad M.J.; Khan M.A.; Husain S.F.; Wuttke F. (My University, 2025)
With the limitation of the land availability in major population centers and the availability of the land to be used as waste management sites, incite is required in improving the ground. Many soil stabilization techniques are available using conventional method. Here, we intend to report a method applying the nanotechnology for ground improvement. T-ZnO is used to improve the uniaxial compressive strength of silty-clay at low liquid limit. Silt soil passing 1mm sieve and T-ZnO between 0-5 wt% is used. It was found that with increasing percentage of T-ZnO up to a threshold, a significant improvement in compressive strength is observed which may be attributed to the peculiar tetrapod shape that acts as reinforcement among silt and clay particles. © 2018 Elsevier Ltd.